EFEKTIVITAS INFUS DAUN SIRIH SEBAGAI ANTIBAKTERI Streptococcus mutans PENYEBAB KARIES GIGI - Dewi Novianti (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2013)
Streptococcus mutans represent most bacterium kondusif cause caries. Society Indonesian have since long recognize leaf of sirih upon which munch with confidence can strengthen tooth and prevent caries. For that require to be research of effectiveness of infus leaf of sirih to S.mutans so that can know optimal potency upon which herb of antibakteri by in-vitro by counting growth of colony amount which growÂ  at each treatment. Research use RAL by 7 treatment and 4 restating. Result of research show to bring of leaf infus of sirih have an effect on very real to growth of bacterium S. mutans. Leaf Infus of sirih effective pursue growth S. mutans.Â Key words: Infus leaf of sirih (Piper betle Linn), bacterium of Streptococcus mutans, growth of colony.